Homonymy in English Language and Means of Its Representation (on Example of Functional Words what and very) - T. S. Ignatyeva; N. A. Antonova (Научный диалог, 2018)
The phenomenon of homonymy of functional words in modern English is considered. The relevance of the work is that the issues of homonymy, in particular one of functional words, are still controversial and not fully studied. In this paper, an attempt is made to identify some of the main provisions that, in the authors’ opinion, will contribute to the differentiation of functional words into closed series and will help to determine the relationship in which these words can be attributed to these closed systems. The authors believe that the definition of a closed series to which a functional word belongs is associated with a number of difficulties, since, firstly, the category of relativity (relations) is not fully understood and its boundaries are not defined, since subjective judgments can be made on the semantic basis with regard to the differentiation of functional or service words, and secondly, because some words are not in one, but in several closed series. The novelty of the study is seen in the fact that by the example of certain functional words ( what and very ), the authors have shown that they can be homonymous words, and their appearance in the language is not the result of conversion, but the result of splitting of multifunctional words expressing relationships.